Răspuns :
Explicație pas cu pas:
5.a)
[tex]- 14 \div ( - 2) - {2}^{3} = 7 - 8 = - 1[/tex]
6.a)
[tex]2 \times |x| - 3 \leqslant 3 \\ 2 \times |x| \leqslant 3 + 3 \\ 2 \times |x| \leqslant 6 \\ |x| \leqslant 6 \div 2 \\ |x| \leqslant 3 \\ - 3 \leqslant x \leqslant 3[/tex]
=> x ∈ {-3; -2; -1; 0; 1; 2; 3}
b)
[tex][4÷(|6-8|-6)+|-5|]^{7} ÷(-2)^{11} = [4÷(| - 2|-6)+5]^{7} ÷( - (2)^{11} )= [4÷(2-6)+5]^{7} ÷( - (2)^{11} ) = [4÷( - 4)+5]^{7} ÷( - (2)^{11} ) = (- 1+5)^{7} ÷( - (2)^{11} ) = (4)^{7} ÷( - (2)^{11} ) = ( {2}^{2} )^{7} ÷( - (2)^{11} ) = {2}^{14} ÷( - (2)^{11} ) = - {2}^{14 - 11} = - {2}^{3} = - 8[/tex]